2016
DOI: 10.14238/sp11.1.2009.1-7
|View full text |Cite
|
Sign up to set email alerts
|

Kelengkapan Imunisasi Dasar Anak Balita dan Faktor-Faktor yang Berhubungan di Poliklinik Anak Beberapa Rumah Sakit di Jakarta dan Sekitarnya pada Bulan Maret 2008

Abstract: Kata kunci: imunisasi dasar, anak balitaAlamat korespondensi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
1
2
0
4
Order By: Relevance
“…8 In this research, we did not get any correlation between the two variables. The same result was done by Albertina et al 9 in their research, with no significance caused by unbalancing total respondents in each respondent group. Hudhah et al 10 have a different conclusion; in their research, they found a correlation between mother attitude towards complete basic immunization.A significant correlation happened because of belief, experience, and support from their public figure to do the basic immunization.…”
Section: Discussionsupporting
confidence: 83%
“…8 In this research, we did not get any correlation between the two variables. The same result was done by Albertina et al 9 in their research, with no significance caused by unbalancing total respondents in each respondent group. Hudhah et al 10 have a different conclusion; in their research, they found a correlation between mother attitude towards complete basic immunization.A significant correlation happened because of belief, experience, and support from their public figure to do the basic immunization.…”
Section: Discussionsupporting
confidence: 83%
“…Albertina, the reason of incompleteness of immunization expressed by the mother is that the child is sick when about to immunize (28.4%) and parents are afraid of the side effect of immunization (23.5%) [1]. The sick child was contraindicateto immunization; however, this reasoncould not be underlined an excuse for having complete basic immunization because the child should have been given it as she/he recovered from the illness.…”
Section: Accordingmentioning
confidence: 99%
“…16 Penelitian yang dilakukan oleh Mathilda menunjukkan tidak ada hubungan antara sikap orangtua terhadap imunisasi dengan kelengkapan imunisasi. 17 Permasalahan tersebut melatarbelakangi penelitian ini untuk mengetahui sejauh mana tingkat pengetahuan dan sikap ayah dalam pemberian imunisasi pada balita. Peranan ayah secara optimal dalam melakukan imunisasi dapat mempengaruhi keberhasilan pemberian imunisasi.…”
Section: Pendahuluanunclassified
“…Hasil penelitian ini sesuai dengan penelitian Mathilda yang menyebutkan bahwa sebagian besar responden memiliki pengetahuan yang baik terhadap imunisasi (86%), dengan sebagian besar ayah memiliki tingkat pendidikan menengah (SMA/ SLTA sederajat). 17 Pengetahuan yang baik dapat dipengaruhi dari tingkat pendidikan responden yang sebagian besar adalah SMA/SLTA (46,6%), dan sebanyak 15 orang responden berpendidikan tinggi (D3/S1). Pendidikan responden merupakan salah satu faktor yang penting dalam meningkatkan pengetahuan karena dengan pendidikan yang baik maka responden dapat menerima segala informasi dari luar terutama tentang pemberian imunisasi dasar pada balita.…”
Section: Pembahasan Pengetahuan Ayah Tentang Pemberian Imunisasi Dasar Pada Balitaunclassified